Model Development of Accounting Internship Efforts in Dealing Industrial Revolution 4.0 - Mohamad Hasanudin; Iwan Budiyono; Mohamad Asrori (Dinamika Pendidikan)
This study aims to develop a model of an internship in the accounting department of Polines in order to achieve competence level KKNI and SKKNI. The basic of this model development is based on the purpose of the Polines Accounting Department interns, students and Company. This research can be categorized as research and development. The data in this study using quantitative and qualitative data such as advice and inputs provided by the students, supervising internships and companies. Quantitative and qualitative data using a questionnaire to assess the feasibility of the proposed model of apprenticeship. The next stage is the development of the model, at this stage derived from theoretical models that sought input from stakeholders through the FGD. The last stage is the implementation of the model is limited. The subjects were 43 students taking internships, industrial 5 and 20 people from higher education institutions. The object of research is the implementation of the accounting department intern program which will be reviewed by: monitoring the implementation of the internship, the duration of the apprenticeship, internship mentor in the field, the suitability of the curriculum to the needs of the world of work, and the skills of students. The results showed that the aspects that need to be improved is the design of the curriculum, internships and assessment management. Results of the model development internship in the Polines accounting department consisting of: (1) model of apprenticeship curriculum development; (2) the management model of apprenticeship; (3) implementing structural model of apprenticeship; (4) models and assessment procedures intern and (5) Industrial Attachment guide.